EVALUASI KINERJA LABORATORIUM LINGKUNGAN DAERAH MELALUI PROGRAM UJI PROFISIENSI PARAMETER Pb, Zn, Mn, Cl-, dan SO4 2- DALAM AIR - Anwar Hadi (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2009)
One of the main uses of proficiency testing schemes is to assess laboratories ability to perform tests competently.Environmental Management Center (PUSARPEDAL – KNLH) conducts proficiency testing program to determinethe performance of individual laboratories for environmental quality tests and to monitor continuing performance.Performance evaluation sample was determined by provider as assign value and distributed to the participants. Theresult of proficiency testing was evaluated by Zscore according to News Statistics NATA’s Proficiency TestingPrograms. In 2008, the participants of proficiency testing program are 52 laboratories which carry out the environmentalquality tests. The result of proficiency testing showed that more than 80% participants have high accuracy andprecision for determination of Pb, Zn and Mn in water using Atomic Absorption Spectrofotometer. Furthermore, thedetermination of Chloride (Cl-) in water was analyzed by argentometric method showed that 73.47% laboratorieshave high accuracy and 87.76% laboratories have high precision. In addition, 65.96% laboratories have highprecision and 87.23% laboratories have high accuracy for determination of Sulfate (SO42-) in water was analyzed byturbidimetric.